Penurunan Kadar Besi dan Mangan Terlarut dalam Air Payau Melalui Proses Oksidasi Menggunakan Kalium Permanganat - J.M. Amin; D.P. Sari (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
The main objective of this research is to reduce the content of iron and manganese dissolved in brackish water as part of the treatment process into clean water. In the early stages, brackish water was coagulated and sediment using PAC 150 ppm. The water is then sent to the unit with KMnO4 oxidation accompanied by stirring. KMnO4 concentration varied three types namely 3.5 ppm, 4.5 ppm, 5.5 ppm. Water analysis is carried out on the raw water and any results of coagulation and sedimentation, until the result of oxidation. Based on the experiments, the best results obtained from using KMnO4 oxidation of 4.5 ppm to lower the Fe content of 1.43 ppm to 0.28 ppm and lower levels of Mn from 0.35 ppm to 0.15 ppm. Coagulation and sedimentation process was instrumental in improving the quality of brackish water, especially in color, taste, pH, and dissolved solids turbidity eligible clean water. Coagulation and sedimentation are also less able to reduce levels of dissolved Fe and Mn. Two stages of treatment (coagulation and sedimentation and oxidation) has been successfully boost water quality and filtration will ease the workload on subsequent processing stages